Preliminary study on willingness to pay for environmentally certified wood products among consumers in Malaysia - Mohamed, Shukri; Ibrahim, Muhammad Lukhman (Science Alert, 2007)
Consumers are expected to demand and would be willing to pay a price premium for environment-friendly products stemming from the growing global environmental consumerism. While consumers in the developed countries are reported to be willing to pay a price premium for environmentally certified wood products, there is hardly any study on consumers’ willingness in other markets. This preliminary study examines consumer willingness to pay a price premium for environmentally certified wood products in Malaysia. Data were obtained using a self-administered questionnaire distributed to 100 systematically-sampled, mall-intercepted respondents. Results indicated that some 38% of the respondents would be willing to pay an average of 14.4% more for environmentally certified wood products.